Democratic Consolidation an Indonesian Unity Perspective - Hadiwasito, Winarto (Lembaga Ketahanan Nasional Republik Indonesia, 2024)
Purpose: This study aims to explore the potential of democratic consolidation in reinforcing national unity in Indonesia, emphasizing the importance of Pancasila values, particularly the third principle, “Indonesian Unity,” in addressing key challenges such as political polarization, social fragmentation, and declining public trust in political institutions. The study underscores practical policy recommendations to bridge the gaps identified. Study Design/Methodology/Approach: Utilizing a qualitative approach, this study employs a comprehensive literature review methodology to analyze theories related to democratic consolidation and national unity. Sources include scholarly articles, books, and relevant documents that discuss the connection between democracy and social cohesion. Foundational theories by Diamond (1999) and Linz and Stepan (1996) are applied as analytical frameworks to evaluate the necessary conditions for democratic consolidation in Indonesia. Findings: The study finds that democratic consolidation can effectively strengthen national unity when supported by robust government performance in legal, bureaucratic, and economic sectors aligned with Pancasila values. Active civil society participation, political society autonomy, and the transparency and accountability of political institutions are essential in fostering public trust and mitigating polarization. Originality/Value: This research enriches existing literature on democratic consolidation and national unity in Indonesia by advocating for inclusive policies and emphasizing the critical role of political education and media literacy for the public. The recommendations presented aim to promote sustainable political stability and social integration, making this study a valuable reference for future research on Pancasila-based democratic consolidation in the global era.